2013
DOI: 10.1080/13803395.2013.778231
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the link between higher order cognitive functions and handedness

Abstract: The study aimed to investigate the hypothesis that in high-functioning individuals the left-handedness phenotype facilitates the performance of executive-related tasks that engage the right hemisphere. The Trail-Making Test and Letter-Number Sequencing, previously indicated to engage the right hemisphere, were applied on 47 right-handers and 50 left-handers. There was a significant effect of handedness on both measures and an interaction effect of gender and handedness on the Trail-Making Test. The findings ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 51 publications
5
31
0
5
Order By: Relevance
“…In addition, a higher degree of right-handedness was associated with somewhat worse performance on the updating tasks, fitting with other evidence that left-or mixed-handedness is associated with better EF performance (e.g., Beratis et al, 2013;Gunstad, Spitznagel, Luyster, Cohen, & Paul, 2007).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In addition, a higher degree of right-handedness was associated with somewhat worse performance on the updating tasks, fitting with other evidence that left-or mixed-handedness is associated with better EF performance (e.g., Beratis et al, 2013;Gunstad, Spitznagel, Luyster, Cohen, & Paul, 2007).…”
Section: Discussionsupporting
confidence: 83%
“…The combined rating on these ladders can predict health-related outcomes as well as, or better than, other more objective measures of SES (e.g., Singh-Manoux, Marmot, & Adler, 2005). Given evidence (albeit mixed) for a greater prevalence of lefthandedness in musicians (Aggleton, Kentridge, & Good, 1994), handedness effects on musical ability (e.g., Kopiez, Galley, & Lee, 2006;Jäncke, Schlaug, & Steinmetz, 1997), and handedness effects on cognitive tasks (also with somewhat mixed findings; e.g., Beratis, Rabavilas, Kyprianou, Papadimitriou, & Papageorgiou, 2013;Nettle, 2003;Powell, Kemp, & García-Finaña, 2012), we administered the Edinburgh handedness inventory (Oldfield, 1971). Finally, bilingualism has been found to predict aspects of EF (e.g., Bialystok, Craik, Green, & Gollan, 2009), so we administered the Language Experience and Proficiency Questionnaire (LEAP-Q; Marian et al, 2007): participants were considered bilingual if they reported speaking a second language with a mean self-rated proficiency of at least 5 on a 1 to 10 scale (where 5 is defined as "adequate"), averaged across ratings of ability in second language speaking, understanding, and reading.…”
Section: Other Background and Demographic Measuresmentioning
confidence: 99%
“…Moreover, left-handedness may facilitate the performance of cognitive tasks requiring greater engagement of right-hemisphere resources, such as visuospatial tasks (e.g. Beratis, Rabavilas, Kyprianou, Papadimitriou, & Papageorgiou, 2013;D'Andrea & Spiers, 2005). However, linguistic skills were not measured specifically in these studies and interest was confined to handedness for noncommunicative activities.…”
Section: Discussionmentioning
confidence: 97%
“…For example, socioeconomic status (SES) correlates with both musical participation (Corrigall, Schellenberg, & Misura, 2013;Kaushal, Magnuson, & Waldfogel, 2011;Norton et al, 2005;Southgate & Roscigno, 2009) and EF abilities (Hackman & Farah, 2009). Handedness is associated with aspects of musical ability (Kopiez, Galley, & Lee, 2006) and with EF performance (Beratis, Rabavilas, Kyprianou, Papadimitriou, & Papageorgiou, 2013), and intelligence (IQ) is linked with both musical training (Schellenberg, 2004;2006) and EF abilities (Friedman et al, 2006). Because these potentially confounding factors have not consistently been assessed, it is not yet clear if specific cognitive abilities are related to musical training or if these relationships reflect differences in other factors.…”
Section: Training and Efsmentioning
confidence: 99%
“…Handedness. Because handedness has been associated with aspects of musical ability (Kopiez et al, 2006) and performance in EF tasks (Beratis et al, 2013), participants completed the Edinburgh handedness inventory (Oldfield, 1971), in which they indicated which hand they preferred to use during various activities (e.g., writing, drawing, or using scissors). This provided a continuous measure of laterality, scored on a scale from -100 (completely left handed) to +100…”
Section: Socioeconomic Status (Ses)mentioning
confidence: 99%